Hypertension outcomes in a fragile setting: predictors of blood pressure reduction and control in the Central African Republic - Doro Altan, Anna Maria; Tchenebou, Boris; Iffio, Kevine; Bortolot, Gabriella; Orlando, Stefano; Guidotti, Giovanni; Petrolati, Sandro; Somse, Pierre; Ciccacci, Fausto (Frontiers in Public Health, 2025)
BackgroundHypertension is a leading contributor to cardiovascular disease and early mortality, and its impact is growing rapidly in low-income countries. In the Central African Republic, the condition represents a major and under-addressed health problem. This study examines the outcomes of hypertension care in Bangui, focusing on factors influencing blood pressure control and reduction (CAR).MethodsThis cross-sectional study analyzed clinical records of hypertensive patients receiving care in Bangui. Demographic and clinical data were collected at baseline and at the most recent follow-up (October-November 2024) to identify factors associated with BP control (<140/90 mmHg) and reduction (decrease of ≥20 mmHg in systolic or ≥10 mmHg in diastolic BP).ResultsWe included 656 patients (69% female, median age 59 years). BP control and clinically significant BP reduction were achieved in 39.5 and 86.7% of patients. Diabetes was an independent predictor of lower BP control (OR = 0.36; 95%CI:0.25–0.52; p < 0.001) and lower BP reduction (OR = 0.56; 95%CI:0.35–0.88; p = 0.012). Chronic kidney disease was associated with lower BP reduction (OR = 0.10; 95%CI:0.02–0.52; p = 0.006). Higher baseline hypertension correlated with BP reduction (Grade 3 hypertension: OR = 88.3; 95%CI:23.4–587; p < 0.001). Older age was associated with BP reduction (OR = 1.16; 95%CI:1.04–1.29; p = 0.007).ConclusionIn Bangui, structured hypertension care proved feasible and led to significant BP reductions, although target control rates remained low, particularly in patients with diabetes and CKD. Strengthening follow-up and access to tailored treatment could improve outcomes in this fragile setting.